"Providing a Roof" and More to Communities Affected by Typhoon Haiyan in the Philippines: the Médecins Sans Frontières Experience. (15th December 2016) - Ali, Engy; Ferir, Marie-Christine; Reid, Tony; Gray, Henry; Van Den Boogaard, Wilma; Gonzales, Christopher; Zachariah, Rony
Abstract: Objectives: Typhoon Haiyan hit the Philippines in November 2013 and left a trail of destruction. As part of its emergency response, Médecins Sans Frontières distributed materials for reconstructing houses and boats as standardized kits to be shared between households. Community engagement was sought and communities were empowered in deciding how to make the distributions. We aimed to answer, Was this effective and what lessons were learned? Methods: A cross-sectional survey using a semi-structured questionnaire was conducted in May 2014 and included all community leaders and 269 households in 22 barangays (community administrative areas). Results: All houses were affected by the typhoon, of which 182 (68%) were totally damaged. All households reported having received and used the housing material. However, in 238 (88%) house repair was incomplete because the materials provided were insufficient or inappropriate for the required repairs. Conclusion: This experience of emergency mass distribution of reconstruction or repair materials of houses and boats led by the local community was encouraging. The use of "standardized kits" resulted in equity issues, because households were subjected to variable degrees of damage. A possible way out is to follow up the emergency distribution with a needs assessment and a tailored distribution. ( Disaster Med Public Health Preparedness . 2017;11:285–289)